Predictors of cyber addiction formation in youth during martial law - Ogorenko, Вікторія; Shornikov, Андрій; Shornikov, Олександр (Psychosomatic Medicine and General Practice, 2026)
Background. Cyberaddiction is a type of behavioral addiction that is often associated with emotional distress, primarily anxiety and depression. During prolonged military stress, the likelihood of developing maladaptive coping strategies - especially excessive Internet use - increases significantly. However, the mechanisms by which anxiety influences cyberaddiction through depression as a mediating factor are still not well understood. Materials and Methods. In May-June 2025, a cross-sectional online survey was conducted among 86 students aged 10 to 28 years. The Young Student Cyber Addiction Scale (YSCAS) was used to assess cyberaddiction, while anxiety was measured using the GAD-2 scale, depression using the PHQ-2 scale, and general distress using the PHQ-4 scale. The analysis involved descriptive statistics, group comparisons, Spearman correlations, logistic regression, mediation analysis (with 5,000 bootstrap samples), and k-means clustering. Results. The median score on the YSCAS was 47 points (interquartile range: 42–58). Respondents identified with cyberaddiction exhibited significantly higher levels of anxiety and depression. Depressive symptoms showed a stronger correlation with addiction (Cohen’s d > 1.0). The correlations were as follows: YSCAS with PHQ-4 (rs = 0.63), YSCAS with PHQ-2 (rs = 0.62), and YSCAS with GAD-2 (rs = 0.54). Mediation analysis confirmed an indirect effect of anxiety on cyberaddiction through depression; the direct effect, after controlling for depression, became insignificant. Discussion. Depression appears to play a crucial role in mediating the relationship between anxiety and cyberaddiction. In wartime, the Internet can serve as an emotional escape, particularly for young individuals experiencing depressive symptoms. Conclusions. Cyberaddiction among youth during wartime is closely linked to psychological and emotional distress, with depressive symptoms serving as a key predictor. These findings suggest that screening for depression could be beneficial in prevention programs aimed at addressing cyberaddiction. Keywords: сyberaddiction, anxiety, depression, youth, martial law, mediator analysis. УДК 616.89-008.441.44:004.738.5-053.81